2018
DOI: 10.1007/s10096-018-3340-5
|View full text |Cite
|
Sign up to set email alerts
|

A survey on practices for active surveillance of carriage of multidrug-resistant bacteria in hospitals in the Autonomous Community of Valencia, Spain

Abstract: A questionnaire-based cross-sectional study was conducted to gather information on current microbiological practices for active surveillance of carriage of multidrug-resistant (MDR) bacteria in hospitals from 14 health departments of the Autonomous Community of Valencia (ACV), Spain, which together provided medical attention to 3,271,077 inhabitants in 2017, approximately 70% of the population of the ACV. The survey consisted of 35 questions on MDR bacteria screening policies, surveillance approach chosen (uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…In this study, we used a multi-body site screening strategy to investigate the rate of MDRB colonization in hematological patients admitted to the hospital for any cause (most frequently receipt of allogeneic or autologous stem cell transplantation, treatment of underlying disease or neutropenic fever) and to what extent this approach allowed us to predict MDRB BSI. Detection of genotypic determinants of antimicrobial resistance in MDRB was performed using a DNA-based microarray, which displays results that fully agree with genome sequencing data [ 26 ]. In line with previous studies [ 30 , 31 ], to increase the rate of detection of MDRB we performed a combination of upper respiratory tract, gastrointestinal tract and axillar sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used a multi-body site screening strategy to investigate the rate of MDRB colonization in hematological patients admitted to the hospital for any cause (most frequently receipt of allogeneic or autologous stem cell transplantation, treatment of underlying disease or neutropenic fever) and to what extent this approach allowed us to predict MDRB BSI. Detection of genotypic determinants of antimicrobial resistance in MDRB was performed using a DNA-based microarray, which displays results that fully agree with genome sequencing data [ 26 ]. In line with previous studies [ 30 , 31 ], to increase the rate of detection of MDRB we performed a combination of upper respiratory tract, gastrointestinal tract and axillar sampling.…”
Section: Discussionmentioning
confidence: 99%
“…All patients colonized with MDRB underwent contact isolation. Surveillance specimens were delivered in AMIES transport medium (cliniswab LTS , Aptaca Spa., Canelli, Italy) to the Microbiology Service and immediately processed in accordance with the Procedures in Clinical Microbiology guidelines issued by the Spanish Society of Infectious Diseases and Clinical Microbiology (SEIMC) [ 26 ]. Swabs were placed in brain–heart infusion broth tubes (BHI; Oxoid Limited, Hampshire, UK) containing a disc of either cefotaxime (30 µg) or imipenem (10 µg), for MDR-Gram negative enrichment and incubated at 37 °C in a CO 2 incubator (Heracell 240i CO 2 incubator, Thermo Fisher Scientific, Langenselbold, Germany) for 24 h. Pharyngeal and nasal swabs were processed individually, while axillary and rectal swabs were combined, as previous data from our group indicated that this strategy yielded comparable results to those obtained by processing both of these specimens individually (not shown) and resulted in lower cost burden.…”
Section: Methodsmentioning
confidence: 99%
“…IRAS são as infecções que ocorrem em pacientes submetidos à procedimentos de assistência à saúde, seja por hospitalização, por comparecimento em consultas ou por realização de exames para diagnóstico ou tratamento. Elas causam grande sofrimento para pacientes e custam muito para as instituições de saúde e para a sociedade (PALMQVIST et al, 2019), pois podem aumentar a permanência dos pacientes no hospital, os custos de tratamento, a morbidade e a mortalidade (DAYYAB et al, 2018;SOLEYMANI et al, 2018;TORMO et al, 2018).…”
Section: Introductionunclassified